Negative Impact of Staying Up Late for Health - Mohammad Dida Wildan Purnama (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
The number of activities that require humans to keep working, doing tasks with short deadlines, and playing gadgets are the main reasons for the problem of lack of need for sleep. This study aims to find out what are the negative impacts of staying up late as well as to find out how much public insight is about the impact of staying up late, how to tighten or eliminate the habit of staying up late and things that need to be prepared when staying up late. The method used is a quantitative method with questionnaire data processing techniques through google form which contains essay questions about the negative impact that respondents feel, how to overcome the habit of staying up late, and what things need to be prepared on the body when they want to do the activity of staying up late. The results of this study indicate that they feel a direct negative impact on the body when they have finished staying up late, they also know how to overcome or eliminate the habit of staying up late, but unfortunately many of them do not know what things the body needs to prepare when they want to do it. staying up late. The conclusion of this study is that the habit of staying up late has become commonplace for most respondents, and many of the respondents immediately felt the negative impact after staying up late